The Analysis of Factors of Pregnant Mother Satisfaction With 10T Antenatal Services in Garut West Java: Analisis Faktor Kepuasan Ibu Hamil Terhadap Pelayanan Antenatal 10T Di Garut Jawa Barat - Dinengsih, Sri; Kundaryanti, Rini; Nurdiani, Leni (Universitas Muhammadiyah Sidoarjo, 2024)
Satisfaction with antenatal care worldwide is influenced by many factors, including access, health resources, government policies, and other factors. In some areas, especially in developing countries, access to health services is often limited, and coverage of antenatal visits is often poor. Inconsistency in providing comprehensive services, lack of medical resources, and less intensive monitoring are examples. This cross-sectional study was conducted with the aim of evaluating the level of maternal satisfaction with 10T antenatal care. Random sampling was the sampling technique. The research tool consisted of a questionnaire on the satisfaction of pregnant women, which consisted of a component of questions on the implementation of classes related to pregnant women. with a Cronbach's alpha coefficient of 0.540, This questionnaire has been tested for validity and reliability. To analyse the level of satisfaction of pregnant women towards 10T pregnancy services at UPT Puskesmas Sukakarya Garut in 2023, this study was conducted with descriptive statistics and Chie Square test. The results showed that there was a significant relationship between satisfaction and pregnancy services 10 T (0.000 <0.05), the truth (0.000 <0.05). Patient satisfaction is strongly influenced by 10T antenatal services. Suggestion: it is expected to increase the reliability of midwives in implementing ANC services to meet the needs of pregnant women so that the quality of antenatal service coverage is well achieved.